2014
DOI: 10.1061/(asce)me.1943-5479.0000216
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Construction Delay Analysis and the Role of Preconstruction Programming

Abstract: Modern construction projects commonly suffer from delay in their completions. The resolution of time and cost claims consequently flowing from such delays continues to remain a difficult undertaking for all project parties. A common approach often relied on by contractors and their employers (or their representatives) to resolve this matter involves applying various delay analysis techniques, which are all based on construction programmes originally developed for managing the project. However, evidence from li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 32 publications
0
22
0
1
Order By: Relevance
“…Doloi (2012), Braimah (2014), and Larsen (2016), in addition to many others, investigated the significant impediments that directly impacted the project's schedule [13,23,24]. The results of these studies indicated weak design elements; poor project planning, site management, and project control; insufficient contractor experience; contract payment problems; equipment availability; weather/environmental conditions; and material supply issues as the primary causes for project delays [13,23,24]. A study by Gebrehiwet et al (2017) revealed 52 of the most likely reasons for project delays; ineffective project scheduling ranked number two, behind deficient project planning [25].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Doloi (2012), Braimah (2014), and Larsen (2016), in addition to many others, investigated the significant impediments that directly impacted the project's schedule [13,23,24]. The results of these studies indicated weak design elements; poor project planning, site management, and project control; insufficient contractor experience; contract payment problems; equipment availability; weather/environmental conditions; and material supply issues as the primary causes for project delays [13,23,24]. A study by Gebrehiwet et al (2017) revealed 52 of the most likely reasons for project delays; ineffective project scheduling ranked number two, behind deficient project planning [25].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Understanding construction delay analysis and the role of preconstruction programming [128], UK In-depth interview; experienced construction planning engineers Complexity, cost, and time. Emphasizes the importance of baseline programs for resolving delay claims.…”
Section: Factors Influencing Delay Claims [127] Indiamentioning
confidence: 99%
“…Apipattanavis et al (2010) and Nguyen et al (2010) investigated the weather impact on the project delay. Braimah (2014) investigated project programming's effect in delay analyzing and claim resolution in the UK construction industry. In this paper, the project's internal environment is best defined as the conditions and events resulting from the action or inaction of the key parties of the project "client, consultant, general contractor and the sub-contractors."…”
Section: R a F T 1 Introductionmentioning
confidence: 99%